Obstacles to the education sector in Iraqi Kurdistan and development proposals in light of some international experiences - an analytical and descriptive study - Muhammad, Dr. Bakhtiar Abdul Rahman Muhammad (Sulaimani Journal for Humanities, 2025)
Education is the fundamental pillar for building a civilized society and achieving sustainable development. It is impossible to imagine the advancement of any country without an effective educational strategy. The education sector in Iraqi Kurdistan suffers from multiple challenges, most notably weak government funding and a lack of financial incentives for teaching staff, along with outdated curricula that are not aligned with the requirements of modern education and the labor market. Furthermore, the impact of internal political crises, the politicization of educational administration, economic problems, and security disturbances resulting from regional interventions have contributed to a decline in motivation among teachers and students, negatively impacting the quality of educational performance. This study adopts a descriptive analytical approach to objectively diagnose the educational situation in the Kurdistan Region, drawing on recent academic studies, research, and reports. It also explores successful international experiences, such as those of Finland, Rwanda, Vietnam, and others, which have been able to overcome their crises through comprehensive educational reforms. The study concludes that advancing and developing education requires effective political and societal will that leads to comprehensive reform and a radical educational vision that restores education to its central position in human development and societal progress.
Keywords: Education in Kurdistan; Curriculum Reform; Government Funding; Educational Challenges; Quality of Educational Outcomes